2002
DOI: 10.1266/ggs.77.11
|View full text |Cite
|
Sign up to set email alerts
|

Functional and physical interaction between Sgs1 and Top3 and Sgs1-independent function of Top3 in DNA recombination repair.

Abstract: A mutant allele of SGS1 of Saccharomyces cerevisiae was identified as a suppressor of the slow-growth phenotype of top3 mutants. We previously reported the involvement of Top3 via the interaction with the N-terminal region of Sgs1 in the complementation of methylmethanesulfonate (MMS) sensitivity and the suppression of hyper recombination of a sgs1 mutant. In this study, we found that several amino acids residues in the N-terminal region of Sgs1 between residues 4 and 33 were responsible for binding to Top3 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
18
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 41 publications
5
18
0
Order By: Relevance
“…In other words, the rescue of the growth defect of rqh1-d rad22-d by deletion of top3 is evidence that Top3 functions independently of Rqh1 but not that Rqh1 functions independently of Top3. This is consistent with work by Onodera et al (43), who reported a functional and physical interaction between Sgs1 and Top3 and an Sgs1-independent function of Top3 in DNA recombination repair (43). In all our experiments we have not been able to separate Rqh1 function from Top3 function.…”
Section: Discussionsupporting
confidence: 93%
“…In other words, the rescue of the growth defect of rqh1-d rad22-d by deletion of top3 is evidence that Top3 functions independently of Rqh1 but not that Rqh1 functions independently of Top3. This is consistent with work by Onodera et al (43), who reported a functional and physical interaction between Sgs1 and Top3 and an Sgs1-independent function of Top3 in DNA recombination repair (43). In all our experiments we have not been able to separate Rqh1 function from Top3 function.…”
Section: Discussionsupporting
confidence: 93%
“…Among the regions showing strongest depletion within edited cells were guide+donors deleting amino acid stretches 1-85, 686-1090 and 1116-1225 within Sgs1, which correspond to the Sgs1-Top3-binding domain, Sgs1-helicase, and RQC domains, respectively (2-tailed t-test, P<0.0001) (Figure 2, Supplementary File 1). These results are consistent with the known mechanism by which Sgs1 functions through the recruitment of accessory proteins (through N-terminal residues) [14][15][16][17][18][19][20][21][22] and by resolution of DNA structural intermediates via its helicase and RecQ domains 23,24 .…”
Section: Resultssupporting
confidence: 88%
“…In most of these reports, alleles expressed from plasmids or integrated at non-native loci were used to study complementation [40,41,45,46,52,[64][65][66][67][68]. To avoid the ambiguities inherent in interpreting growth or lack of growth in cells transformed with a plasmid as well as to avoid potential position effects for loci integrated elsewhere, all mutant alleles used in this study were integrated at the SGS1 genomic locus (Table 1) [53,54].…”
Section: Mutant Sgs1 Alleles Integrated At the Genomic Locusmentioning
confidence: 99%